Intelligent early warning system for epidural acute hematomas - Doğuç, Özge (International Balkan University, 2020)
Epidural hematoma (EAH) is the accumulation of blood in the space between the outer membrane of the brain (dura mater) and the bone. Acute subdural and epidural hematoma appears on CT scan as a hyper-dense collection often located in brain convexity. Such bleeding can become fatal by increasing intracranial pressure and creating a mass effect. Therefore, it is very important to recognize these bleedings promptly in an emergency trauma setting. Thus, early diagnosis is essential to reduce mortality and morbidityratesin these cases. There has been a growing interest in artificial intelligence (AI) and machine learning (ML) algorithms for diagnostics in medical fields. In this study, a supervised learning method was used in which the decision tree ML algorithm is trained with the patients'statuses(EAH or Normal). This study proposes an early warning system (EWS) that scans all cranial CTs obtained at the trauma center. The EWS in this study, trained with CT scans from about 100 patients, can predict EAH with 100% accuracy usingimage recognition and supervised learning algorithms. Each MR section obtained for each patient is individually analyzedbyimage processing and EAH detection is made. For this, the decision tree method, which is a supervised learning algorithm, was trained and used to detect EAH in MR sections. The algorithm has been developed in such a way that it will immediately alert the emergency physician and consultant neurosurgeon by e-mail when it detects EAH in more than 10 sections in any patient.

Epidural hematom (EAH), beynin dış zarı (dura mater) ile kemik arasındaki potansiyel boşlukta kan birikmesidir. Akut subdural ve epidural hematom, BT taramasında genellikle beyin konveksitesinde yer alan hiper yoğun bir koleksiyon olarak görünür. Bu tür kanamalar kafa içi basıncını artırarak ve kitle etkisi yaratarak ölümcül hale gelebilir. Bu nedenle, acil travma ortamında bu kanamaların derhal tanınması çok önemlidir. Bu nedenle bu vakalarda mortalite ve morbiditeyi düşürmek için erken tanı şarttır. Tıbbi alanlarda teşhis için yapay zeka (AI) ve makine öğrenimi (ML) algoritmalarına son zamanlarda artan bir ilgi vardır. Bu çalışmada, karar ağacı ML algoritmasının hastaların durumlarıyla (EAH veya Normal) eğitildiği denetimli bir öğrenme yöntemi kullanılmıştır. Bu çalışma, travma merkezinde elde edilen tüm kraniyal BT'leri tarayan bir erken uyarı sistemi (EWS) önermektedir. Bu çalışmadaki EWS, yaklaşık 100 hastadan alınan CT taramaları ile eğitilmiştir, görüntü tanıma ve denetimli öğrenme algoritmaları ile%100 doğrulukla EAH'yi tahmin edebilir.Her hasta için elde edilen her MR kesiti teker teker görüntü işleme analizinden geçirilir ve EAH tespiti yapılır. Bunun için bir denetimli öğrenme algoritması olan karar ağacı yöntemi eğitilerek MR kesitlerinde EAH saptaması için kullanılmıştır. Algoritma herhangi bir hastada 10’dan fazla kesitte EAH tespit ettiğindeacil durum hekimine ve danışman beyin cerrahına e-posta ile anında uyarı verecek şekilde geliştirilmiştir.
Epidural akut hematomlar için akıllı erken uyarı sistemi
Keywords: Acute; Epidural Acute Hematomas; Warning System; Akut; Epidural Akut Hematomlar; Uyarı sistemi